Therapeutic potential of casticin in alleviating ovarian torsion/detorsion-induced ovarian and lung injuries - Ersen Eraslan; Ayhan Tanyeli̇; Mustafa Guler; Fazile Nur Eki̇nci̇ Akdemi̇r; Ömer Topdaği; Şahin Yazici; Derya Güzel Erdoğan; Esra Çinar Tanriverdi̇; Selim Çomakli (Iranian Journal of Basic Medical Sciences)
Objective(s): Ovarian torsion is a critical gynecological emergency caused by the twisting of the ovary around its supporting structures, resulting in compromised blood flow and potential ovarian damage. Ovarian torsion/detorsion (T/D) can lead to severe complications, including infertility, if not promptly addressed. This study aimed to investigate the therapeutic effects of casticin (CAST) on ovarian and lung tissue injuries induced by a bilateral ovarian T/D model in rats.Materials and Methods: Experimental animals were randomly allocated into groups of sham, T/D, CAST 5 mg/kg, and CAST 10 mg/kg. Ovarian and lung tissues were subjected to biochemical, histopathological, and immunohistochemical analyses.Results: In the T/D group, markers of oxidative stress and inflammation, including myeloperoxidase (MPO) activity, malondialdehyde (MDA), oxidative stress index (OSI), tumor necrosis factor-alpha (TNF-α), and 8-hydroxy-2’ deoxyguanosine (8-OHdG), were significantly elevated (P<0.05). Conversely, superoxide dismutase (SOD) activity and total antioxidant status (TAS) levels were notably decreased (P<0.05). CAST administration significantly attenuated tissue damage by reducing oxidative stress and inflammatory markers while enhancing antioxidant defense (P<0.05).Conclusion: CAST demonstrated a therapeutic effect against ovarian and lung tissue damage induced by T/D, suggesting that it may serve as a potential therapeutic agent for treating ovarian T/D-related injuries. These findings underscore the potential of CAST in clinical settings, particularly as a novel intervention to mitigate complications associated with I/R injuries in gynecological emergencies.